2012
DOI: 10.1016/j.chembiol.2012.07.016
|View full text |Cite
|
Sign up to set email alerts
|

A Potent and Selective S1P1 Antagonist with Efficacy in Experimental Autoimmune Encephalomyelitis

Abstract: Lymphocyte trafficking is critically regulated by the Sphingosine 1-phosphate receptor-1 (S1P(1)), a G protein-coupled receptor that has been highlighted as a promising therapeutic target in autoimmunity. Fingolimod (FTY720, Gilenya) is a S1P(1) receptor agonist that has recently been approved for the treatment of multiple sclerosis (MS). Here, we report the discovery of NIBR-0213, a potent and selective S1P(1) antagonist that induces long-lasting reduction of peripheral blood lymphocyte counts after oral dosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 29 publications
6
93
0
3
Order By: Relevance
“…VPC23019 S1P 1 S1P 3 (Davis et al, 2005) VPC44116 S1P 1 (Foss Jr. et al, 2007) TASP0277308 S1P 1 NIBR0213 S1P 1 (Quancard et al, 2012) ML056 (R)-W146 S1P 1 Tarrason et al, 2011) (S)-FTY720 vinylphosphonate S1P 1 S1P 3 S1P 4 (Valentine et al, 2010) JTE013 S1P 2 (Osada et al, 2002); in combination with SK1-I, see (Chen et al, 2015) Compound 22 S1P 2 (Kusumi et al, 2015) TY52156 S1P 3 SPM242 S1P 3 ML131 S1P 4 (Oldstone et al, 2010) …”
Section: Compoundmentioning
confidence: 99%
“…VPC23019 S1P 1 S1P 3 (Davis et al, 2005) VPC44116 S1P 1 (Foss Jr. et al, 2007) TASP0277308 S1P 1 NIBR0213 S1P 1 (Quancard et al, 2012) ML056 (R)-W146 S1P 1 Tarrason et al, 2011) (S)-FTY720 vinylphosphonate S1P 1 S1P 3 S1P 4 (Valentine et al, 2010) JTE013 S1P 2 (Osada et al, 2002); in combination with SK1-I, see (Chen et al, 2015) Compound 22 S1P 2 (Kusumi et al, 2015) TY52156 S1P 3 SPM242 S1P 3 ML131 S1P 4 (Oldstone et al, 2010) …”
Section: Compoundmentioning
confidence: 99%
“…4E). Treatment with the S1P 1 -selective functional antagonist NIBR-0213 (38) showed fivefold increase of 1-kDa Alexa Fluor 555-cadaverine accumulation in brain parenchyma at 6 h after injection, but not at 48 h after injection of NIBR-0213 (Fig. 4 F and G).…”
Section: Reversible and Size-selective Opening Of Bbb By Pharmacologicalmentioning
confidence: 99%
“…Finally, a series of N-biaryl(hetero) arylsulfonamide compounds originally reported in the patent literature and later optimized for pharmaceutics properties to produce NIBR-0213 (Berst et al 2007;Quancard et al 2012) have shown comparable efficacy to FTY720-P in mouse experimental autoimmune encephalomyelitus) models of human multiple sclerosis.…”
Section: Non-lipid Antagonistsmentioning
confidence: 98%